2007
DOI: 10.15517/rbt.v56i4.5776
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Helminth Parasites of the fish Synodontis clarias (Siluriformes: Mochokidae) from Lekki lagoon, Lagos, Nigeria

Abstract: A total of 362 specimens of the fish Synodontis clarias were randomly selected and subjected to parasitological examination for helminth parasites. They were collected over a period of one year from Lekki lagoon, Lagos, Nigeria. The prevalence of gastrointestinal infection was 38.7%. The helminth worms found include two cestodes, Proteocephalus spp., Wenyonia acuminata, and a nematode species, Raphidascaroides. Male specimens (196) presented a higher rate of infection (37.8%) than female specimens (166) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
33
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 7 publications
13
33
2
1
Order By: Relevance
“…The possible reason for this relationship smallest fed less amount of foods hence gained less immunity compared the large fish. This is in agreement with (Akinsanya et al, 2008) who reported that smaller fish were more infected compared to larger probably due to their nature of acquired immunity with age. In contrast, the present study disagrees with findings reported (Ashade et al, 2013) whom both reported that bigger (and therefore possibly mature) fish have more parasites compared to small fish because they feed more on diverse food sources thereby exposing them to more parasitic infestation.…”
Section: Discussionsupporting
confidence: 93%
“…The possible reason for this relationship smallest fed less amount of foods hence gained less immunity compared the large fish. This is in agreement with (Akinsanya et al, 2008) who reported that smaller fish were more infected compared to larger probably due to their nature of acquired immunity with age. In contrast, the present study disagrees with findings reported (Ashade et al, 2013) whom both reported that bigger (and therefore possibly mature) fish have more parasites compared to small fish because they feed more on diverse food sources thereby exposing them to more parasitic infestation.…”
Section: Discussionsupporting
confidence: 93%
“…The high prevalence for S. clarias may be attributed to the suitability of the fish host in provision of appropriate ecological requirements of the parasite (Akinsanya et al, 2008;Lagrue et al, 2011). Similarly, the high nutritional content of the S. clarias intestine may possibly account for their preference, restriction and abundance in them (Akinsanya et al, 2008). Two parasite genera, Camallanus and Capillaria, were present in all fish species.…”
Section: Discussionmentioning
confidence: 98%
“…Neoechinorhynchus, Pomphorhynchus, Acanthocephalus and the unidentified acanthocephalans showed the highest abundance in the Warri River, and were limited almost to S. clarias. The high prevalence for S. clarias may be attributed to the suitability of the fish host in provision of appropriate ecological requirements of the parasite (Akinsanya et al, 2008;Lagrue et al, 2011). Similarly, the high nutritional content of the S. clarias intestine may possibly account for their preference, restriction and abundance in them (Akinsanya et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Stevens and White (1987) show that improvement in teacher motivation has benefits for students and teachers. In Nigeria, the quality of education at all levels (primary school, secondary school and tertiary institutions) has long been adjudged as substandard, half-baked, and poor while the causes have been attributed to poor funding, overpopulation of students, inadequate and outdated infrastructures, and above all, poor remuneration and motivation of the academic staff (see : Mafiana, 2011;Ekundayo, and Ajayi, 2009;and Akinsanya, 2007). In essence, staff motivation being a strong determinant of staff contribution to teaching can be used as a weapon to reverse the declining standard of university education in the country.…”
Section: Discussion Of Findingsmentioning
confidence: 99%